Effects of NAA and BA on Lily (lilium spp.) Propagation by Scaling - Fathi , Shams M.; Attiya, Hatim J. (Iraqi Journal of Science, 2021)
The experiment was executed at the Botanical Garden- college of Science, university of Baghdad, Iraq. The period was from November 2016 to March 2017, on the scales of lilium ( Peral Carolina) belonging to the asiatic hybrids imported from the Netherlands. The scales of lily treated with naphthyl acetic acid (NAA)(0,25,50) mg/l and benzyl aminopurine (BA)(0,10,20) mg/l twice after planting to improve flowering characters of hybrid lily cultures . It was observed that at the concentration BA 20 mg/l and NAA 50 mg/l increased the number of bulbues formed about 0.8% and the number of bulbs as 11.3%, while the root length decreased with the same concentration about 5.7%. The fresh weight of the buds, the length of the buds and the number of roots at the concentration of BA 20 mg/l and NAA 0 mg/l was increased about (0.6%, 2.2%, 66%), respectively . The fresh weight of bulblets increase as 0.8% when the BA concentration was 10 mg/l and NAA 50 mg/l. Therefore we can conclude that the best concentration recommended for hormonal interference is BA 20 mg /l and NAA 50 mg /l, where the number of bulbs formed and number of bulblets was increased.